Max runs away - Steel, Danielle; Rogers, Jacqueline (New York, N.Y. : Delacorte Press, 1990)
Jealous of the time his parents spend with his baby brother and sister, seven-year-old Max leaves home but soon learns the dangers of running away
Keywords: Runaway children -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Safety -- Juvenile fiction